Isolated perforation of fourth part of Duodenum following Blunt Abdominal Trauma - Maharjan, Prabir; Bharti, Shiv Vansh; Khadka, Digbijay Bikram; Karki, Anup; Gnyawali, Arun (Journal of Nepalgunj Medical College, 2022)
Introduction: Isolated duodenal injuries are rare in blunt abdominal trauma. These present a significant challenge for management because of the associated injuries and its difficult anatomical accessibility. Case presentation: A 20years male presented to the Emergency department following a bike accident sustaining injury over face, chest and abdomen, 6hours after the incident. His vitals were unstable so he was resuscitated and admitted in Intensive Care Unit. He had generalized abdominal tenderness without rigidity. Contrast enhanced computed tomography of abdomen and pelvis was suggestive of hollow viscus perforation. He underwent exploratory laparotomy and primary repair for isolated perforation at fourth part of duodenum. He was discharged on his ninth postoperative day. Conclusion: Rare injuries following blunt abdominal trauma should be considered and early intervention is necessary.